PERLINDUNGAN HUKUM BAGI TENAGA KERJA WAKTU TERTENTU DI KABUPATEN INDRAGIRI HILIR - Syariffudin; Nurhan (JURNAL HUKUM DAS SOLLEN, 2023)
The basis of labor law in Indonesia is regulated in Article 27 paragraph (2) of the 1945 Constitution which states that "every citizen has the right to work and a living worthy of humanity". This article reflects that work is very important to create prosperity for everyone. Certain Time work agreements are regulated in Article 59 paragraph (1) of Law Number 13 of 2003 concerning Employment. Certain Time Workers means all workers who are bound by a Certain Time Work Agreement. The provisions regarding Specific Time Work Agreements are regulated in the Decree of the Minister of Manpower and Transmigration No. 100/MEN/IV/2004 concerning Implementation of Specific Time Work Agreements. In the implementation of the Specific Time Work Agreement (PKWT) in Indragiri Hilir Regency, there are indications that many irregularities have occurred. Therefore, there is a need for legal protection for these workers.